Anode oxidation of salts of organic acids - Ільчак, О.Б.; Зубенко, С.О.; Ледовських, В.М. (Proceedings of National Aviation University (archive), 2008)
The resulted results on research of anode ocsidation of salts of carbon acids with the purpose of estimation of possibility of electrochemical regeneration of worked motor oils. It is shown the control of decline of maximum diffusive current and direct measuring of decline of concentration of solutions (photometry, potentiometry), that in the conditions of motion of reaction Colbe there is effective transformation of acid products of ocsidation of oils with a high output.